Doing Thesis While Working Part Time, Why Not? A Case Study of Self-Efficacy in College Students - Ramadhanti, Auliya; Dirham, Izza Fadhlinah; Hadi, Indri Gemi Nastiti; Putra, Rahman Pranovri; Azizah, Hanna Jessica Al (CV. Doki Course and Training, 2025)
Many individuals fail to achieve their goals because of their low self-efficacy. This research was initiated from a case that many researchers found in the surrounding environment, especially the campus environment. Researchers often meet students who do part-time jobs in between their activities as students. This phenomenon makes researchers interested in conducting research on students who work part-time during the thesis preparation period to see how the student's self-efficacy is. The research then uses a qualitative approach with a case study method, with the subject collection technique using purposive sampling technique, with data collection using interviews. The results showed that the subject under study was able to achieve all aspects of self-efficacy. The subjects succeeded in motivating and convincing themselves that they could by managing their time well, not giving up easily and being confident that they would graduate even with a busy schedule. And find a way to get up and succeed in completing their assignments.